1998
DOI: 10.1007/s004420050629
|View full text |Cite
|
Sign up to set email alerts
|

Is leaf-level photosynthesis related to plant success in a highly productive grassland?

Abstract: We addressed the question: "Are short-term, leaf-level measurements of photosynthesis correlated with long-term patterns of plant success?" in a productive grassland where interspecific competitive interactions are important. To answer this question, seasonal patterns of leaf-level photosynthesis were measured in 27 tallgrass prairie species growing in sites that differed in species composition and productivity due to differences in fire history. Our specific goals were to assess the relationship between gas e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 37 publications
4
25
1
1
Order By: Relevance
“…C4 prairie grasses are the latest species to come into leaf in prairie communities and lose little new foliage when burnt in spring. This, in combination with their higher leaf level photosynthesis (McAllister et al, 1998) results in them out-competing C3 prairie forbs under a frequent burning regime (Seastedt et al, 1991). Whilst this is the general pattern, in studies conducted over a 20-year period, Tester (1996) found that cover values of prairie forbs increased with fire frequency.…”
Section: Introductionmentioning
confidence: 85%
“…C4 prairie grasses are the latest species to come into leaf in prairie communities and lose little new foliage when burnt in spring. This, in combination with their higher leaf level photosynthesis (McAllister et al, 1998) results in them out-competing C3 prairie forbs under a frequent burning regime (Seastedt et al, 1991). Whilst this is the general pattern, in studies conducted over a 20-year period, Tester (1996) found that cover values of prairie forbs increased with fire frequency.…”
Section: Introductionmentioning
confidence: 85%
“…We expected interannual variability to have a smaller effect on A CO 2 relative to that of intra-annual rainfall variability, because A CO 2 in these grasses decreases strongly with soil moisture depletion, and recovery is often slow when soil moisture is restored, especially after extended drought (Knapp, 1985;Heckathorn et al, 1997). Leaf level photosynthesis has been associated with long-term plant success in this grassland (McAllister et al, 1998), and the ability to track soil moisture variability is crucial to the success of the grasses (Swemmer et al, 2006;Nippert et al, 2006a). The finding that A CO 2 was strongly correlated with 15 (Table 1) suggests that on average, A CO 2 was strongly coupled to interannual climate variation and associated interannual differences in soil water supply.…”
Section: Interannual Variability Caused Greater Effects Than Increasementioning
confidence: 99%
“…For example, grass ANPP and A CO 2 was more highly correlated with 15 than was forb ANPP and A CO 2 (Table 1). C 4 grasses such as A. gerardii and S. nutans typically have higher photosynthetic rates and experience greater variation in plant water status than forbs (Knapp, 1984;Turner et al, 1995;McAllister et al, 1998;Nippert et al, 2006a). Stable isotope studies of soil water use by C 4 grasses at the Konza site shows that they rely on surface soil water regardless of landscape location, soil water availability, or time of year, while forbs increase their dependence on deeper soil moisture as surface soils dry (Nippert and Knapp, 2007a, b).…”
Section: Interannual Variability Caused Greater Effects Than Increasementioning
confidence: 99%
“…Photosynthetic activities can be represented as the growth potentials of the plant (Mooney 1972, Walters et al 1993, McAllister et al 1998, Knee and Thomas 2002. Chlorophyll (Chl) a fluorescence of photosystem 2 plays an important role in the response of leaf photosynthesis to environmental stresses (Baker 1991).…”
mentioning
confidence: 99%